2020
DOI: 10.3389/fmicb.2019.02984
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP-CRP Modulates the Cell Morphology of Klebsiella pneumoniae in High-Glucose Environment

Abstract: Bacteria can modify their morphology in response to environmental stimuli for survival or host defense evasion. The rich glucose in vivo or in the Luria-Bertani (LB) medium shortened the cell length of Klebsiella pneumoniae. The environmental glucose decreased the levels of cyclic AMP (cAMP) and the transcription of crp, which declined the cAMP-cAMP receptor protein (cAMP-CRP) activity. The cell length of crp deletion mutant was significantly shorter than that of the wild type (0.981 ± 0.057 µm vs. 2.415 ± 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
0
11
1
Order By: Relevance
“…Further, CRP has been implicated in the regulation of multiple stress and virulence factors, together with antibiotic resistance. 53–55 , 63–65 Using an isogenic Δ crp mutant we could not observe, at least in the tested experimental conditions, any role for this gene in modulating fitness in an immune-activated scenario; however, we report that crp is per se crucial to establish colonization of the gut in the first place. This is in keeping with our failure to detect glucose in the mouse intestine via metabolomics approaches.…”
Section: Discussioncontrasting
confidence: 58%
“…Further, CRP has been implicated in the regulation of multiple stress and virulence factors, together with antibiotic resistance. 53–55 , 63–65 Using an isogenic Δ crp mutant we could not observe, at least in the tested experimental conditions, any role for this gene in modulating fitness in an immune-activated scenario; however, we report that crp is per se crucial to establish colonization of the gut in the first place. This is in keeping with our failure to detect glucose in the mouse intestine via metabolomics approaches.…”
Section: Discussioncontrasting
confidence: 58%
“…Studies of a strain of K. pneumoniae strain NTUH-K2044 showed that the mutant with the Δcrp deletion was characterized by increased HMV and ability to form biofilms and produce fimbriae [76,98]. Excess glucose in the external environment decreased the CRP level, leading to increased cps gene expression [79].…”
Section: Hypermucoviscosity and Regulators Of Capsule Synthesismentioning
confidence: 99%
“…However, there was no significant difference in the level of transcription in the high-glucose environment. 35 Therefore, the regulation of ompA by high glucose is still controversial. This investigation revealed that high glucose enhanced the mRNA of ompA and the addition of exogenous cAMP suppressed its enhancement.…”
Section: Discussionmentioning
confidence: 99%